El Uso De Tecnología Ppm Mejora La Gestión Estratégica De Los Proyectos De La Estafeta Docente. Estudio De Caso: Facultad De Recursos Naturales, Escuela Superior Politécnica De Chimborazo, Ecuador - Santillán, Carlos Arturo Jara; Merino, Christiam Paúl Aguirre; Rodríguez, Patricio Lozano; Guadalupe, Carla Sofía Arguello; Zambrano, Ginno Sidney Jarrín; Izurieta, Johanna Elizabeth Ayala (European Scientific Journal, ESJ, 2017)
A study of PPM methodologies, strategic management, and teaching baton of Escuela Superior Politécnica de Chimborazo (ESPOCH) for implementing a software solution in managing projects of the Faculty of Natural Resources was performed. Through research, it was determined that there is a close relationship between the use of PPM and reducing the problems and performance improvement projects. This is in addition to the portfolio management project which has differences of tracking, time, resources, and the scope of traditional project management. It provides a global view thereof that strategic management must involve all levels of the organization. This will anticipate a correct decision. Also, with respect to projects in the Faculty of Natural Resources, 98% of teachers and the total authorities considered the urgent need to implement a software for strategic management of projects in the faculty. This is because 83% of them were conducted, while 80% performed linkage. A set of tools for application development under the cascade methodology for the monitoring and evaluation of projects entitled SIMEP was determined. By implementing SIMEP based on the use of PPM, the Faculty of Natural Resources provided information management project based on its submission, approval, execution, completion and delivery of results, and reporting activities, thereby enabling timely decision making.